Wstępne wyniki badań grodziska w Zgłowiączce, gm. Lubraniec, woj. włocławskie, w 1988 r. - Andrzejewska, Aldona (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The studies were conducted by the Archaeological Department of University of Łódź charged with the task by the Provincial Conservator of Monuments in Włocławek. It was the second season of investigations. In 1988, excavations of 15 x 2,5 m were located in the eastern part of the castle on the W-E axis, from the coping of the dike directed to the maidan. According to the stratography observed there two settlement s levels related to the second stage of fortifications of the castle and one settlement’s level related to the first stage of castle’s fortification were discovered. An unfortified settlement was registered under the heaped levers of the dike and cultural stratifications of the castle. According to the earthenware material the discovered settlement s levels dated back to the second half of the 12th century and to the 13th century. In historical sources no reference to the castle was found. Documents are related to the Zgłowiączka village itself and salt-works working in the village. The first reference comes from 1155, from the bulla of the Pope Hadrian IV and it contains the list of possessions of the monastery of canons regular in Czerwińsk where the salt-works in Zgłowiączka is mentioned among others. The castle must have played an important economic role the castellany of Włocławek and Brzesk. Since it was situated on the Zgłowiączka river at the ford where there was a road leading to Radziejów and Kruszwica, in the village with market and salt-works.